Comparative evaluation of wear resistance of CAD-CAM zirconia and cast cobalt chromium alloy for indirect restorations against human enamel - An In Vitro study - N Arul Kumar; Jayakrishnakumar Sampathkumar; Hariharan Ramakrishnan; Vallabh Mahadevan (Wolters Kluwer Medknow Publications, 2020)
Purpose of the Study: To comparatively evaluate the wear resistance of two different posterior indirect restorative materials against human enamel. Materials and Methods: Two different posterior indirect restorative materials of ten in each Group-I (Monolithic zirconia) (n = 10) and Group-II (Cast cobalt chromium) (n = 10) were formed into disc and used as a substrate for the wear test. Freshly extracted mandibular first premolars were used as a pin (antagonist) (n = 20). Pin-on-disc wear testing machine was used to simulate the masticatory parameters and evaluation of the wear parameters was done after 1,20,000 cycles, with load of 40N for specific duration. Data related to wear testing procedure were tabulated and evaluated. Results were statistically analyzed using Mann-Whitney test and Wilcoxon signed rank test. Results: Mean surface roughness value (Ra value) obtained for Group-I disc test samples showed no statistical significance (P value < 0.05). Mean wear rate value of test disc samples was statistically significant between Group-I and Group-II (P value < 0.05). Mean surface roughness value was statistically significant between Groups-I and II before and after wear test (P value < 0.05). Conclusion: From the results obtained, it was found that the Group-I (Monolithic zirconia) exhibited higher wear resistance than Group-II (cast cobalt chromium) and causes less wear to the opposing enamel antagonist.